Pengaruh Pemberian Makanan Tambahan dan Terapi Akupresure terhadap Peningkatan Berat Badan Balita pada Usia 1-5 Tahun di Wilayah UPT. Puskesmas Tanjung Palas Tahun 2023 - Irma Irma; Novi Pasiriani; Faridah Hariyani; Grace Carol Sipasulta (Lembaga Publikasi Ilmiah Nusantara, 2023)
Toddlers 1-5 years old golden period of growth and development, especially the brain, inadequate nutritional intake due to lack of appetite related to increased activity, facilitate exposure to infectious diseases, malnutrition / poor. To cope with it, additional feeding is necessary. Acupressure therapy a certain point addresses the problem of appetite of toddlers. The purpose of this study was to determine the effect of supplementary feeding and acupressure therapy on the body weight of toddlers aged 1-5 years in the Tanjung Palas health center area. Quasi-experimental research with pretest design and posttest control group design, total sampling technique for toddlers aged 1-5 years malnourished as many as 30 samples in the Tanjung Palas Health Center area with SD (-3 SD <-2 SD), weight for 2 months does not increase or remains, infants without chronic diseases, do not experience neurological disorders. The intervention group was 15 toddlers and the control was 15 toddlers. The data were processed by univariate analysis using frequency distributions and bivariate, Paired t-test hypothesis test and dependent t-test. Characteristics of high school education rate 60%, income 2-3 million 60% and IRT employment 80%. The control group before treatment with a mean value of 10.713 and after a mean value of 10.9667. The intervention group before the treatment had a mean value of 10.1267 and after the treatment a mean value of 10.4667. Paired T test mean value -.3400 with p value 0.126. T test p value 0.006 Ho rejected, there is an increase in toddler weight 1-5 years after administration and acupressure.